2014
DOI: 10.1128/aac.00022-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fluorescence-Based Method for Antibabesial Drug Screening

Abstract: In vitro evaluation of chemotherapeutic agents against Babesia and Theileria parasites has become routine, and the effectiveness of these chemicals is usually determined by comparing the parasitemia dynamics of untreated and treated parasites. Although microscopy is widely used to calculate parasitemia, several disadvantages are associated with this technique. The present study evaluated a fluorescence-based method using SYBR green I stain (SG I) to screen antibabesial agents in in vitro cultures of Babesia bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
1
23
1
3
Order By: Relevance
“…Morphological and degenerative changes were also observed in parasites treated with gedunin. An alternative method was later developed and optimized to microscopy screening of Babesia, a fluorescence-based method [104,105]. The newly developed method for drug evaluation against B. bovis was successfully achieved; the IC 50 value obtained, 19 µM [104], was comparable to the previously published microscopy-based value, 21.7 µM [103], with no statistically significant (p < 0.05) difference between them.…”
Section: Antiparasital Activitymentioning
confidence: 72%
See 1 more Smart Citation
“…Morphological and degenerative changes were also observed in parasites treated with gedunin. An alternative method was later developed and optimized to microscopy screening of Babesia, a fluorescence-based method [104,105]. The newly developed method for drug evaluation against B. bovis was successfully achieved; the IC 50 value obtained, 19 µM [104], was comparable to the previously published microscopy-based value, 21.7 µM [103], with no statistically significant (p < 0.05) difference between them.…”
Section: Antiparasital Activitymentioning
confidence: 72%
“…An alternative method was later developed and optimized to microscopy screening of Babesia, a fluorescence-based method [104,105]. The newly developed method for drug evaluation against B. bovis was successfully achieved; the IC 50 value obtained, 19 µM [104], was comparable to the previously published microscopy-based value, 21.7 µM [103], with no statistically significant (p < 0.05) difference between them. Initially, this method was not suitable for a large scale screening, since medium had to be replaced every day, but that was later overcome [105].…”
Section: Antiparasital Activitymentioning
confidence: 72%
“…They concluded that prevention and control programs against sources and reservoirs of zoonoses should be planned by public health and veterinary officers based on reliable information from systematic surveillance. Guswanto et al (2014) evaluated a fluorescence-based method using SYBR green I stain (SG I) to screen anti-babesial agents in in vitro cultures of Egyptian B. bovis. The linearity between relative fluorescence units (RFU) and parasitemia was found to be well correlated with a 0.9944 goodness-of-fit (r(2)) value.…”
Section: Some Selected Egyptian Publicationsmentioning
confidence: 99%
“…The main aim of the synthesis of this compound was to produce a chemical that would be used in combating diseases caused by blood parasite infections such as Trypanosoma sp and Babesia sp [3]. DIAC has been utilized in as the main trypanocidal and babesicidal drug in different regions of the world because of its excellent therapeutic index [4,5,6,7]. Even though DIAC has been widely studied over the last 60 years, there have been extensive studies in recent times on it owing to its therapeutic potentials and pleiotropic effects [3,8].…”
Section: Introductionmentioning
confidence: 99%